MOTIVASI PENGUNJUNG TERHADAP TERAPI KESEHATAN DI OBJEK WISATA PEMANDIAN AIR PANAS BORA - I Made Lafran Adi Pramana; Komang Triawati; I Gede Adiyana Putra (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2026)
Bora Hot Spring Tourism Object in Sigi Regency is one of the natural tourism destinations with significant potential for health tourism development. This study aims to analyze visitors' motivations for undertaking health therapy at Bora Hot Spring, identify the perceived therapeutic benefits, and examine the factors influencing their visitation decisions. The study employed a descriptive qualitative approach using field research methods. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data presentation, and conclusion drawing and verification techniques. The findings indicate that visitors' motivations are influenced by internal (push) factors, including the desire for relaxation, relief from muscle fatigue, treatment for certain health conditions, and psychological well-being. External (pull) factors include the attractiveness of the natural scenery, the availability of natural hot springs, health therapy facilities, and a comfortable tourism environment. The available therapies, including hot spring bathing, reflexology, and sauna, provide various health benefits such as improved physical fitness, relaxation, reduced muscle and joint pain, and support for recovery from certain health conditions, particularly skin diseases and mobility disorders. The study concludes that the combination of therapeutic health benefits and the attractiveness of the natural tourism environment constitutes the primary motivation for visitors to choose Bora Hot Spring Tourism Object as a health tourism destination.